Antioxidant Potential of Selected Oil Plants of Brassicaceae Burnett - Rakhmetov, Dzhamal; Vergun, Olena; Rakhmetova, Svitlana; Fishchenko, Valentyna (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The economically important species of genus Brassica L. were investigated in this study. Alcohol and water plant extracts of cultivars and varieties of Brassica campestris and B. rapa were inspected on antiradical activity by DPPH-method (with 2,2-diphenyl-2-picrylhydrazyl). Obtained extracts were measured on a spectrophotometer at wavelength 515 nm. Antiradical activity of methanol extracts was in the range from 34.29 (B. rapa subsp. rapifera Metzger (f. biennis), f. EOTRFO) to 58.09 % (B. campestris f. biennis D.C., cv. Oriana). Water extracts demonstrated this activity in range from 58.18 (B. campestris f. biennis D.C., cv. Oriana) to 84.25 % (B. campestris f. biennis D.C. × B. rapa L., f. EOTFVS). Antioxidant activity (AA) of extracts of investigated plants was expressed in ascorbic acid equivalent (mg g-1 AAE). The highest AA of methanol extracts was found for B. campestris f. biennis D.C. × B. rapa L., cv. Fitopal (86.07 mg g-1 AAE), the lowest one – for B. rapa subsp. rapifera Metzger (f. biennis), f. EOTRFO (52.78 mg g-1 AAE). Maximal AA of water extracts was registered for B. campestris f. biennis D.C. × B. napus f. biennis D.C., cv. Innovacia (121.77 mg g-1 AAE), minimal – for B. campestris f. biennis D.C. × B. rapa L., f. EOTFVS (85.18 mg g-1 AAE).